Determination of cellular protection and leukemic cell inhibition by herbal extracts in cow urine. - Akansha Tripathi; Sameena Akhtar; CS Senthil Kumar; S Ravi; Ritu Singhal; Rachna Jain; Sunil Kumar; Ragini Gothlwal; Narayanan Ganesh (International Journal of Phytomedicine, 2014)
Cow urine is used as a therapeutic agent and a most valuable secretion of animal origin and herbs have been used as a antioxidant and chemotherapeutic agents,therefore we evaluated the cell protective and cell inhibitory activity of different herbs/spices which was prepared in cow urine( in order to enhance the activity) by MTT assay, and performed the above assay in blood cancer cells viz.ALL, AML, CML type of cancers.The results suggest that revealed that the drugs tested Ajwain, garlic, Dhania, Satavar, and Guduchi prepared in cow urine showed significant antioxidant activity or cell proliferative activity whereas, the extracts such as Dalchini, evaporated cow urine showed an excellent cell inhibition activity in all the three types of cancers viz. ALL, AML and CML. Kalmegha is showing cell inhibitory property for ALL cells but not for AML and CML cells, similarly Garlic showed cell inhibition property for AML but not for ALL and CML cells.